2019
DOI: 10.18551/rjoas.2019-11.28
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Broilers Given Eugenol of Clove Leaf Essential Oil as a Feed Additive

Abstract: Clove (Syzygium aromaticum L.) leaf extraction can produce 2-4% essential oil, containing 70-90% eugenol. Clove essential oil has biological activities, such as antibacterial, antifungal, insecticidal and antioxidant properties, and is used traditionally as a savoring agent and antimicrobial material in food. It becomes the basis for this research on the use of eugenol of clove leaf essential oil as a feed additive for broilers. Experimental treatments consisted of E0 (without the use of eugenol), E1 (0.5% eug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Moreover, this effect is not exclusive for garlic and its products. Tahir, et al [ 53 ] observed that using incremental doses of another phytochemical, eugenol, in broiler feed, affected the palatability, decreasing the ADFI while raising the inclusion of eugenol. Regarding to ION birds, our data suggests that it has no significant effect on performance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this effect is not exclusive for garlic and its products. Tahir, et al [ 53 ] observed that using incremental doses of another phytochemical, eugenol, in broiler feed, affected the palatability, decreasing the ADFI while raising the inclusion of eugenol. Regarding to ION birds, our data suggests that it has no significant effect on performance.…”
Section: Discussionmentioning
confidence: 99%
“…Minyak cengkeh memiliki kandungan antioksidan yang lebih tinggi dibadingkan dengan kandungan antioksidan yang terdapat pada lemon, anggur, dan ketumbar (Musta dan Nurliana, 2019). Menurut Tahir et al (2019) bahwa eugenol memiliki sifat anti mikroba dan anti oksidan yang dapat meningkatkan pertumbuhan ternak. Selain itu, daun cengkeh dapat menghasilkan 2-4% minyak atsiri dengan kadar 70-90%.…”
Section: Pendahuluanunclassified
“…Tingginya nilai daya cerna pada penelitian ini diduga disebabkan pemberian minyak atsiri daun cengkeh yang tinggi. (Tahir et al, 2019) melaporkan bahwa dengan menambahkan 0,5-1% eugenol minyak atsiri daun cengkeh dalam pakan dapat meningkatkan daya cerna pakan, sehingga kebutuhan untuk pertumbuhan terpenuhi walaupun asupan pakan cenderung menurun; semakin tinggi penambahan minyak atsiri daun cengkeh dalam pakan, maka semakin rendah populasi Salmonella sp. dan Esherechia coli dalam saluran pencernaan yang berdampak pada meningkatnya kecernaan nutrisi pakan.…”
Section: Daya Cerna Lemakunclassified
See 1 more Smart Citation
“…Eugenol content of clove leaf oil is 79.72% and antioxidant is 42.26 ppm. The higher the eugenol content of clove leaf oil, the higher the antioxidant content (Tahir, et al 2019. Razafimamonjison, et al( 2015 stated that the smell of clove leaf is caused by the content of eugenol which is the main compound (72-90%) and functions as an antiseptic and anesthetic.…”
Section: Original Researchmentioning
confidence: 99%